Features of blood`s microcirculation at physical loads - Stanishevska, Tetana; Gorna, Оksana; Horban, Daria; Yusupova, Olga (ScienceRise: Biological Science, 2020)
This research deals with the study of blood microcirculation peculiarities. Materials and methods. 72 students of Bogdan Khmelnytsky Melitopol State Pedagogical University, aged 18–19, were examined. The experimental research consisted of the study of blood microcirculation functional state by means of Laser Doppler flowmetry (LDF) method. It helped to evaluate the state of tissue blood-circulation and to detect individual-typological peculiarities of blood microcirculation under the influence of physical activity (before and after exercise). Results. Three types of blood microcirculation were identified by using LDF-metry. The normoemic type of blood microcirculation, characterized by the superposition of oscillatory rhythms and reflected the balance of the mechanisms of regulation of microcirculation. The hyperemic type, characterized by a «monotonous» LDF-gram with a high parameter of microcirculation, which reflects the relative predominance of metabolic mechanisms in the regulation of microcirculation. The hypoemic type, characterized by a «monotonous» LDF-gram with a low parameter of the microcirculation parameter, which reflects the decrease of vasomotor mechanisms in the regulation of microcirculation. According to the LDF-metric data, the examined students under intensive physical activity have a significant increase in microcirculatory status: by 6 % of the microcirculation parameter, by 28 % of the mean square deviation and by 45 % of the initial value of the coefficient of variation. Conclusions. This dynamics of microcirculation shows that under the influence of physical exertion, a person creates significant functional reserves for the redistribution of blood flow and for more perfect intraorgan capillary blood flow. It was found, that in the process of physical activity, morpho-functional rearrangements of the human cardiovascular system occur. This reaction is formed by several components of blood microcirculation: blood flow in the transport direction, regulating blood supply in accordance with the needs of tissues and the exchange component of the histochemical barrier